Evaluasi Pengelolaan Limbah Bahan Berbahaya & Beracun (Limbah B3) di Rumah Sakit - Nurul Anjana Nasution; Adinda Putri Chania; Puti Sri Komala (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
This study evaluated the management and handling of toxic and hazardous wastes in hospitals based on current regulations. The research was conducted at X Type C Hospital from 5 September 2022 to 28 October 2022. The data analysis of hospital toxic and hazardous waste sorting, packaging, storage, transportation and handling refers to the Minister of Environment and Forestry No. 56 of 2015. Hospital hazardous waste consists of medical and non-medical waste generated from polyclinic rooms, inpatient, pharmacy, laboratory, radiology and emergency room facilities. Medical waste generation is 68.83 kg/day, non-medical waste of TL lamps is 154.8 kg for 6 months, and used lubricant oil is about 20 L for 1 year. The hazardous waste has been sorted by type, namely infectious waste and sharps waste, while the non-medical waste consists of TL lamps and used oil. Transfer points are signposted, away from food storage and preparation areas, and are easily accessible. Transport to the hazardous waste treatment facility is provided by four vans three times a week. The processing of medical waste is carried out by third parties who have manifest documents. With the exception of sharps containerisation and storage duration, all components of the hospital's hazardous waste management are compliant.